Dinâmica de encosta em compartimento dissecado da superfície de cimeira de Pinhão/Guarapuava no quaternário tardio - Gazola , Karina de Cássia (2020)
The present work aimed to characterize a hillslopes dynamics in compartment dissected from the surface of the pinhão / guarapuava in the upper quaternary, based on the description of the surface formations by the litho-; alo- and chronostratigraphic criteria. The study object consists of a stratigraphic section in a context of paleovalleyhead located in the dissected border of Pinhão/Guarapuava-PR surface, individualized from a cross section of highway. To reach the objective, it was necessary to identify and describe the stratigraphic section; characterization of stratigraphic records; the chronology for the process recorded in the superficial formations; and the verification and correlation of the pedostratigraphic records of studies of the region with global paleoclimatic variations. The records found on the slope were individualized, being a paleosol buried with hydromorphic characteristics and cut by a linear incision, stratigraphic deposits of co-aluvium, an intermediate colluvial sequence of granular structure and na upper colluvial sequence. The last three records were responsible for the filling the gully, and the presence of alterite was identified throughout the slope base. These sedimentary records are the results of morphogenesis that favored the filling the gully, generating an inversion of relief in the area. Twenty-four pedostratigraphic horizons were characterized, the micromorphological description revealed that the records submitted to the method are of allochthonous origin and were transported by different processes, being channeled surface runoff (co-alluvial sequence), surface runoff (intermediate colluvial sequence) and earth flow (upper colluvial sequence). The data obtained by isotopic carbon analysis, suggest that the records follow an isotopic variation, consisting of C3 plants (shrubs and trees) and mixture (C3 + C4). From the LOE and 14C dating it was possible to establish the geochronological records 6Cb (18,850 ± 2,350 ky BP), 13Cb (24,750 ± 2,780 ky BP) and 16CAb (25,495 ± 25,013 ky BP), which were established between the Last Interstate ( EIM3) and the Last Glacial Maximum (EIM2). The phases of pedogenesis and morphogenesis identified in the Pinhão / Guarapuava summit surface are similar to those identified in the Planalto de Palmas / Caçador.